2016
DOI: 10.1038/srep27902
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles defeat p53-positive and p53-negative osteosarcoma cells by triggering mitochondrial stress and apoptosis

Abstract: Loss of function of the tumour suppressor p53 observed frequently in human cancers challenges the drug-induced apoptotic elimination of cancer cells from the body. This phenomenon is a major concern and provides much of the impetus for current attempts to develop a new generation of anticancer drugs capable of provoking apoptosis in a p53-independent manner. Since silver nanoparticles (AgNPs) possess unique cytotoxic features, we examined, whether their activity could be exploited to kill tumour suppressor-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
71
4
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 53 publications
6
71
4
4
Order By: Relevance
“…6 In recent years, gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs), 7 in particular, have been in the focus of increasing interest due to their simple synthesis and desirable biological activities (ie, antitumor, antibacterial, antiviral and antifungal effects). 8,9 We have reported that the cytotoxic features of AgNPs can be exploited to kill p53 tumor suppressor-deficient 10 as well as multidrug-resistant cancer cells, 11 providing some further details to the mechanism of AgNP-induced antitumor actions. In recent years, several studies have also demonstrated that AgNPs, synthesized either by conventional chemical reduction methods, physical techniques or by different biological entities, exhibit potent inhibitory effects against Gram positive and Gram negative bacterial species and induce cytotoxicity in various pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…6 In recent years, gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs), 7 in particular, have been in the focus of increasing interest due to their simple synthesis and desirable biological activities (ie, antitumor, antibacterial, antiviral and antifungal effects). 8,9 We have reported that the cytotoxic features of AgNPs can be exploited to kill p53 tumor suppressor-deficient 10 as well as multidrug-resistant cancer cells, 11 providing some further details to the mechanism of AgNP-induced antitumor actions. In recent years, several studies have also demonstrated that AgNPs, synthesized either by conventional chemical reduction methods, physical techniques or by different biological entities, exhibit potent inhibitory effects against Gram positive and Gram negative bacterial species and induce cytotoxicity in various pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The strong oxidative activity of Ag NPs surfaces and the release of Ag ions to the biological environment also attributes to their antimicrobial activity (Zhang et al 2014). Previously conducted toxicological evaluations of Ag NPs have also indicated that it kill cells through a Trojan-horse type mechanism, suggesting that the release of Ag þ ions upon Ag NPs intracellular accumulation (Kov acs et al 2016). The release of Ag þ ions induces reactive oxygen species (ROS) generation thereby unbalancing the redox homeostasis of the cell (Kov acs et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previously conducted toxicological evaluations of Ag NPs have also indicated that it kill cells through a Trojan-horse type mechanism, suggesting that the release of Ag þ ions upon Ag NPs intracellular accumulation (Kov acs et al 2016). The release of Ag þ ions induces reactive oxygen species (ROS) generation thereby unbalancing the redox homeostasis of the cell (Kov acs et al 2016). This furthermore produces adverse effects on the overall cell functionality inducing cytotoxic and immunological responses and ultimately cell death (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of AgNP action is in fact driven mainly by these ions, leading to the generation of reactive oxygen species finally causing cell death. 37,38 Therefore, the less silver ions are released, the weaker will be the AgNPinduced cellular toxicity. Surprisingly, in every biological test we performed, bigger sized GT-AgNPs resulted to be more effective than smaller C-AgNPs.…”
mentioning
confidence: 99%